Chirality of Liquid Crystals Formed from Achiral Molecules Revealed by Resonant X‐Ray Scattering. Issue 41 (11th June 2020) - Lewandowski, Wiktor; Vaupotič, Nataša; Pociecha, Damian; Górecka, Ewa; Liz‐Marzán, Luis M.
Abstract: Intensive research on chiral liquid crystals (LCs) has been fueled by their actively tunable physicochemical properties and structural complexity, comparable to those of sophisticated natural materials. Herein, recent progress in the discovery of new classes of chiral LCs, enabled by a combination of nano‐ and macroscale investigations is reviewed. First, an overview is provided of liquid crystalline phases, made of chiral and achiral low‐weight molecules, that exhibit chiral structure and/or chiral morphology. Then, recent progress in the discovery of new classes of chiral LCs, particularly enabled by the application of resonant X‐ray scattering is described. It is shown that the method is sensitive to modulations of molecular orientation and therefore provides information hardly accessible by means of other techniques, such as the sense of helical structures or chirality transfer across length scales. Finally, a perspective is presented on the future scope, opportunities, and challenges in the field of chiral LCs, in particular related to nanocomposites. Abstract : Chirality in liquid crystalline systems is reviewed, with special emphasis on advanced examination techniques that enable unmasking of the internal structure and morphology of novel mesophases. Particular emphasis is placed on the benefits of resonant X‐ray techniques. The application potential of chiral liquid crystals in nanocomposites is provided.